The Influence of Family Leadership Style on Family Business Performance - Redi Ismail; Ihsanul Kamil; Safira Nada Januar; Mira Nurfitrya; Azizah Fauziyah (Journal of Economics, Social, and Humanities, 2023)
Family businesses play a significant role in the global economy, yet leadership styles within families are often unique and complex. Performance in family business has been a focal point concerning the influence of family leadership style on family business performance. This research aims to analyze the influence of leadership style within the family context on family business performance. The study employs a quantitative method with a descriptive-verification approach to collect and analyze data. Quantitative data is obtained through surveys distributed to family members involved in the family business. The research focuses on family businesses owned by Entrepreneurship students at Universitas Pendidikan Indonesia. These family businesses are selected to represent diversity in leadership styles and their business sizes. The results of this study indicate that family leadership style significantly influences family business performance. The findings provide valuable insights into how families can enhance their business performance through effective family leadership styles.